Dampak Penggunaan Artificial Intelligence (AI) pada Mahasiswa Teknologi Informasi: Studi kasus di Politeknik eLBajo Commodus - Isnain Saif Saifullah; Gracedelia Jeanywealsny Ngasa; Roberto Florio Tito Tarang; Filomena Selsagus Mhutri; Laurensius Sandrio (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2024)
In today's digital context, the development of information and communication technology (ICT) has had a significant impact on various aspects of life, including in education. One of the latest innovations in ICT is Artificial Intelligence (AI), which has the ability to imitate human intelligence in solving problems and making decisions. This study aims to investigate the application of Artificial Intelligence (AI) in the learning process of students, as well as its impact on motivation and interest in learning. The findings of the study indicate that Artificial Intelligence (AI) can enhance the learning experience through access to more interactive materials and rapid feedback. However, the application of Artificial Intelligence (AI) also faces challenges, such as data privacy issues and equality of access, which need to be considered. Therefore, it is very important for students, especially in the field of information technology, to understand how Artificial Intelligence (AI) works and its limitations, and to use it wisely. This study is expected to provide deeper insight into students' readiness to face an increasingly automated world of work and encourage the development of skills relevant to Artificial Intelligence (AI) technology.